2021
DOI: 10.1098/rsos.210802
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analyses reveal infectious disease-driven selection in a free-ranging ungulate

Abstract: Infectious diseases play an important role in wildlife population dynamics by altering individual fitness, but detecting disease-driven natural selection in free-ranging populations is difficult due to complex disease–host relationships. Chronic wasting disease (CWD) is a fatal infectious prion disease in cervids for which mutations in a single gene have been mechanistically linked to disease outcomes, providing a rare opportunity to study disease-driven selection in wildlife. In Wyoming, USA, CWD has graduall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 61 publications
(94 reference statements)
2
18
0
Order By: Relevance
“…We are not aware of any study evaluating differential harvest of deer with different PRNP genotypes; however, a number of deer studies evaluating genotypic differences in CWD status have also assumed harvest was not based on PRNP genotype (see Ketz, Johnson, et al., 2019; Robinson, Samuel, Johnson, et al., 2012). PRNP genotype distributions have consistently demonstrated that the frequency of least susceptible PRNP alleles are uncommon (LaCava et al., 2021; Monello et al., 2017; Robinson, Samuel, O’Rourke, et al., 2012). These findings have led to the hypotheses that the low frequency of least susceptible PRNP genotypes is a result of non‐random mating or reduced fitness in the absence of CWD (Robinson, Samuel, Johnson, et al., 2012; Robinson, Samuel, O’Rourke, et al., 2012; Wolfe et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We are not aware of any study evaluating differential harvest of deer with different PRNP genotypes; however, a number of deer studies evaluating genotypic differences in CWD status have also assumed harvest was not based on PRNP genotype (see Ketz, Johnson, et al., 2019; Robinson, Samuel, Johnson, et al., 2012). PRNP genotype distributions have consistently demonstrated that the frequency of least susceptible PRNP alleles are uncommon (LaCava et al., 2021; Monello et al., 2017; Robinson, Samuel, O’Rourke, et al., 2012). These findings have led to the hypotheses that the low frequency of least susceptible PRNP genotypes is a result of non‐random mating or reduced fitness in the absence of CWD (Robinson, Samuel, Johnson, et al., 2012; Robinson, Samuel, O’Rourke, et al., 2012; Wolfe et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When pathogens affect individual fitness, there is an added potential for natural selection of less susceptible genotypes. However, documenting pathogen‐driven genetic selection in wildlife populations is difficult due to potentially complex host–pathogen interactions (LaCava et al., 2021). Moreover, development of strategies to manage disease‐affected wildlife populations can be challenging because of the potentially complex interaction between harvest, host demographics, disease dynamics and genetic selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations